Hubungan Pola Asuh, Pola Makan Dan Penyakit InfeksiDengan Kejadian Gizi Buruk Pada Balita Di KabupatenMagetan Tahun 2016 - Isnaini, Nurul; , Yuli Kusumawati, SKM, M.Kes (Epid); , Kusuma Estu Werdhani, SKM, M.Kes (2016)
Malnutrition becomes society health problem which can influence quality of the next generation. Malnutrition in community health centre of Panekan area in 2015 was about 0,6% and in 2016 was about 0,78%. While in community health centre of Karangrejo in 2015 was about 1,6% and in 2016 was about 1,02%. This research aims to analyze the relationship among the way of mothering, the way of eating, and infectious disease toward children under five with malnutrition in Magetan Regency. This research was observational research with case-control approach. Population of this research was the whole children on age 6-59 mounths which affected malnutrition and nutrient. The samples election are around 54 children under five used fixed disease technique and control samples are 108 children whose house are near the cases. The statistic test technique used Chi Square and stratification test used Mantel-Haenszel. The result of this research showed that there was relationship among the way of mothering (p=0,000), the way of eating (p=0,000), and infectious disease (p=0,000) with malnutrition in Magetan Regency. While the result of stratification of economi status was not as confounding variable in relationship between the way of mothering with malnutrition (ΔPOR=2,2%), but in relationship between the way of eating with malnutrition (ΔPOR=15%) and relationship between infection disease and malnutrition (ΔPOR=27%), economic status was as confounding variable.